Living on the Edge : Risk, Protection, Behavior, and Outcomes of Argentine Youth - Justesen, Michael (Washington, DC: World Bank, 2012)
Risk and protective factors influence behaviors and outcomes for youth. While risk factors expose youth to risk-taking behavior that compromises well-being and hinders personal development, protective factors mediate risk and act as protective mechanisms that insulate youth from negative outcomes. This paper groups youth by risk levels using a cluster analysis methodology, and identifies the risk and protective factors that characterize these groups. Using data from a new household survey covering youth in four urban areas of Argentina in 2005, youth are clustered by characteristics in relation to family and health, education and income, substance abuse, and crime and violence as indicators of risk and protective factors, and behaviors and consequences. Almost half of Argentine youth are at an elevated risk level, and one in four is at serious risk of experiencing negative outcomes or already suffering the consequences. The findings show, for example, that higher income protects against risk factors, such as an insecure neighborhood, and facilitates youth attending school. Furthermore, parents' lack of education is negatively related to the behaviors and outcomes of their children.